齿轮传动热分析综述 - 王忠达; 刘邦才; 闫业矗; 蔺东龙 (Jixie chuandong)
Gear drive technology is widely applied in the automotive,construction machinery and aviation industry.However,during the transmission of the gear in meshing,a lot of heat will be generated due to the relative sliding friction between two tooth surfaces,which will not only reduce the transmission efficiency,but also can cause local thermal deformation and thermal stress due to local high temperature,and then causes the scuffing and pitting of gear.Combining the present progresses of gear thermal analysis,the theoretical calculations,numerical analysis and test of thermal analysis are summarized,and the emphasis of gear thermal analysis is points out.